Medicolegal Aspects of Examination of Silent Witnesses in the Form of Bloodstains: A Narrative Literature Review - Ilfatul, Arifanda (Sriwijaya Journal of Forensic and Medicolegal, 2023)
Crime has become a subculture, or a separate part of the culture public modernity is no longer just a deviation of social institutions. With advances in science and technology, investigators and experts can search for evidence through scientific analysis. This literature review aimed to describe the examination of silent evidence in the form of bloodstains which are generally found at murder crime scenes. The most common bloodstains found at crime scenes are on the floor. This is due to the drops of blood that fall to the floor following the direction of the earth's gravitational force. There are several things that must be considered in observing blood spots, namely the color of the blood, the estimated volume, and the color of the floor where the blood drips. Examination methods developed by forensic researchers around the world in assessing bloodstains include using electron paramagnetic resonance (EPR), reflectance spectroscopy, and high-performance liquid chromatography (HPLC). In conclusion, the assessment of the color of the bloodstains as a silent witness can provide clues regarding the age of the bloodstains and the time of the crime.